Iodide, iodate & dissolved organic iodine in the temperate coastal ocean - Matthew R. Jones; Rosie Chance; Thomas Bell; Oban Jones; David C. Loades; Rebecca May; Liselotte Tinel; Katherine Weddell; Claire Widdicombe; Lucy J. Carpenter (Frontiers in Marine Science, 2024)
The surface ocean is the main source of iodine to the atmosphere, where it plays a crucial role including in the catalytic removal of tropospheric ozone. The availability of surface oceanic iodine is governed by its biogeochemical cycling, the controls of which are poorly constrained. Here we show a near two-year time series of the primary iodine species, iodide, iodate and dissolved organic iodine (DOI) in inner shelf marine surface waters of the Western English Channel (UK). The median ± standard deviation concentrations between November 2019 and September 2021 (n=76) were: iodide 88 ± 17 nM (range 61-149 nM), iodate 293 ± 28 nM (198-382 nM), DOI 16 ± 16 nM (<0.12-75 nM) and total dissolved iodine (dIT) 399 ± 30 nM (314-477 nM). Though lower than inorganic iodine ion concentrations, DOI was a persistent and non-negligible component of dIT, which is consistent with previous studies in coastal waters. Over the time series, dIT was not conserved and the missing pool of iodine accounted for ~6% of the observed concentration suggesting complex mechanisms governing dIT removal and renewal. The contribution of excess iodine (I*) sourced from the coastal margin towards dIT was generally low (3 ± 29 nM) but exceptional events influenced dIT concentrations by up to ±100 nM. The seasonal variability in iodine speciation was asynchronous with the observed phytoplankton primary productivity. Nevertheless, iodate reduction began as light levels and then biomass increased in spring and iodide attained its peak concentration in mid to late autumn during post-bloom conditions. Dissolved organic iodine was present, but variable, throughout the year. During winter, iodate concentrations increased due to the advection of North Atlantic surface waters. The timing of changes in iodine speciation and the magnitude of I* subsumed by seawater processes supports the paradigm that transformations between iodine species are biologically mediated, though not directly linked.